PWE-061 Split-dose Moviprep (low Volume Peg) And Afternoon Colonoscopy: A Step In The Right Direction. (9th June 2014) - Ghuman, S; George, P; Jones, K; Khan, H
Abstract : Introduction: Good bowel preparation is essential for optimal mucosal visualisation during colonoscopy. The aim of this retrospective study was to evaluate the efficacy of three types of bowel preparation – Picolax (sodium picosulphate), single dose Moviprep and split-dose Moviprep. Methods: Two groups of patients; bowel cancer screening and symptomatic patients – who underwent colonoscopy at our institution over a 12-month period were identified. Within the two groups, 50 patients receiving each type of bowel preparation were selected providing a total of 300. Data collected included subjective endoscopist rating of bowel preparation quality (good, satisfactory, poor), depth of insertion, timing of endoscopy and polyp detection. Results: In symptomatic patients, 94% prescribed split-dose Moviprep had good or satisfactory bowel preparation with an unadjusted caecal intubation rate of 96%. 80% prescribed single dose Moviprep and 84% prescribed Picolax received the same rating with a caecal intubation rate of 88 and 92% respectively. More afternoon colonoscopies received a 'good' bowel preparation rating (65.3 vs 30.8%, p value <0.001) and more polyps (52.6 vs 47.4%) were detected regardless of preparation type. Moviprep was associated with the highest polyp detection rate (61 vs 34%, p value 0.03). In screening patients, 98% prescribed split-dose Moviprep had good or satisfactory bowel preparation. 94% prescribed single dose Moviprep and 90% prescribed picolax achieved the same rating. There was no significant difference in caecal intubation or polyp detection within the screening group. Conclusion: Split-dose Moviprep and colonoscopy performed in the afternoon are two independent factors facilitating better bowel cleansing and higher polyp detection. Disclosure of Interest: None Declared.